Использование языка VBA в качестве механизма моделирования физических процессов - Касымова, А.Г.; Шевченко, И.М. (My University, 2016)
The article describes about methods of teaching physics with using information technology. An attempting to use joint use of traditional teaching methods (a task solving) and programmed (to build a computer model of this task). As the programming language used by the built-in Microsoft Office language VBA. An example of a practical task, used in the framework of this method.
Keywords: computer simulation; visualization of physical processes; the learning process; teaching method; Microsoft Office